Aspects of the ecology and behaviour of Orange River Francolin (Francolinus levaillantoides) in the Windhoek district, Namibia - Scholtz, Melanie Constance (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.